Draft Seventh Five-Year Plan, 1985-90 and Annual Plan, 1985-86 Maharashtra State Part Two - Planning Commission (Planning Commission, 1985)
Abstract Statement indicating sub-sector wise outlays and expenditure Statement indicating scheme wise outlays and expenditure Statement indicating selected physical targets and achievements Statement indicating outlays and expenditure in respect of Minimum Need-Programme Statement indicating physical targets and achievements in respect of Minimum Needs Programme Statement indicating outlays and expenditure in respect of Centrally Sponsored Abstract Statement indicating outlays and expenditure in respect of Tribal Area Sub-Plan Abstract Statement indicating outlays and expenditure in respect of Special Component Plan Abstract Statement of District Plan outlays
Government of Maharashtra, Planning Department